2016
DOI: 10.1007/s10458-016-9338-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of commitment and level of participation in public goods games

Abstract: Before engaging in a group venture agents may require commitments from other members in the group, and based on the level of acceptance (participation) they can then decide whether it is worthwhile joining the group effort. Here, we show in the context of public goods games and using stochastic evolutionary game theory modelling, which implies imitation and mutation dynamics, that arranging prior commitments while imposing a minimal participation when interacting in groups induces agents to behave cooperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 66 publications
3
67
0
Order By: Relevance
“…Through a finite population game dynamics analysis, Han et al (2017a) essentially found a similar evolutionary cycle, from unconditional defectors to conditional cooperators, then to unconditional cooperators, and then to unconditional defectors again. In contrast, there is a remarkable difference between these two models.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Through a finite population game dynamics analysis, Han et al (2017a) essentially found a similar evolutionary cycle, from unconditional defectors to conditional cooperators, then to unconditional cooperators, and then to unconditional defectors again. In contrast, there is a remarkable difference between these two models.…”
Section: Discussionmentioning
confidence: 93%
“…If one breaks the commitment he or she has to pay a fine. It has been shown that a large fine enhances the success of commitment strategies (Han et al, 2013(Han et al, , 2015a(Han et al, , 2017a. Another possible way to suppress those who make a fake commitment would be to exclude them from other games in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the capacity to create, and commit to, prior agreements (Nesse, 2001;Frank, 1988;Han et al, 2017Han et al, , 2015a) has been proposed as an evolutionarily viable strategy inducing cooperative behaviour in the context of cooperation dilemmas; namely, the Prisoner's Dilemma (PD) (Han et al, 2013) and the Public Goods Game (PGG) (Han et al, 2017). It provides an alternative to different forms of punishment against inappropriate behaviour and of rewards to stimulate the appropriate one (Martinez-Vaquero et al, 2015;Sasaki et al, 2015;Powers et al, 2012).…”
Section: Introductionmentioning
confidence: 99%